Ice and Flame: "Project" Collections in Contemporary Russian Speculative Fiction. (1st October 2016) - Volodikhin, Dmitrii
Abstract : Dmitrii Volodikhin considers two recent collections of Russian fantastika that largely disprove/go against the recent downturn in the genre's quality.